Study of endocrinological complications in children with beta thalassemia major - Jain, Jigar K.; Vaishnav, Jolly G.; Vohra, Arif S.; Shah, Mansi; Goyal, Anika; Kansagara, Mit; Gohil, Priya (International Journal of Contemporary Pediatrics, 2022)
Background: Thalassemia is the commonest hemoglobinopathy in our country of which β thalassemia is most common. More and more endocrinological complications are seen in current scenario in children usually more than 10 years of age with significant iron overload due to inadequate iron chelation. Aim of the study is to understand the common endocrinological complications and the key factors for their prevention. Methods: A prospective analytical study was done at a tertiary care centre, civil hospital, Ahmedabad in children between 9-18 years of age over period of 1 month to determine the prevalence of endocrinological complications and their correlation with mean serum ferritin levels in beta thalassemia patients. Results: Total 48 children enrolled during study period. Mean serum ferritin level 3179±788 ng/ml. Out of 48, 20 children (41.66%) having endocrinological complications. Most commonly observed endocrinological complication was growth retardation in which 17 children (35.41%) were undernourished and 13 children (27%) found to have stunted growth. Delayed puberty was observed in 7 children (14.58%). Hypothyroidism observed in 4 children (8.33%). Five patients (23.8%) with mean serum ferritin level <2500 ng/ml and 15 patients (55.5%) with mean serum ferritin level beyond 2500 ng/ml developed endocrinological complications which statistically significant (p=0.02). Conclusions: Endocrinological complications in adolescent children with thalassemia major were mild in severity in our study and observed when the serum ferritin went beyond 2500 ng/ml. Thus, these children should be managed at a tertiary care centre. Early identification and multidisciplinary treatment are necessary for early treatment as well as prevention of endocrinological complications.